Supraspinatus tendon measurement using high frequency ultrasound in Sudanese pediatrics. Issue 1 (December 2021) - Elgyoum, Ala M.A.; H. Mohammed, Marwa; Abdelrahim, Ahmed; Zidan, Mogahid M.A; Alsaadi, Mohammed; Salih, Mohammed; Elhaj, Mona; Davidson, Rob; Mahmoud, Mustafa Z.
ABSTRACT: The frequency of rotator cuff diseases makes shoulder ultrasound (US) one of the most prevalent musculoskeletal ultrasound (MSK US) applications. Sudanese children's supraspinatus tendon thickness and width were measured as part of this study to help with the early detection of supraspinatus tendon disease. Between August and December 2020, researchers conducted this cross-sectional investigation. There were 114 participants in the study, ranging in age from 4 to 14 years, with 81 males (71.1%) and 33 females (28.9%) participating. Study variables were incorporated into a customized data collection sheet used to gather the information. The supraspinatus tendons were found to be 5.31 ± 0.69 mm in thickness and 26.91 ± 2.06 mm in width. While the supraspinatus tendon thickness was correlated significantly ( p < 0.01) to age ( r = 0.280), weight ( r = 0.254), and height ( r = 0.335) in terms of their p -values, it was not correlated significantly to body mass index (BMI) ( p > 0.05). A significant correlation ( p < 0.01) was found between the supraspinatus tendon's width and age ( r = 0.519), weight ( r = 0.507), height ( r = 0.489), and BMI ( r = 0.309). Standard reference values for supraspinatus tendon measures were found in Sudanese children. US musculoskeletal assessments of the supraspinatus tendons are proposed as a method for detecting anomalies in these tendons.